Strategy of Gamification, Product and Pricing: Does It Matter on Buying Interests of Fore Coffee consumers - Rakhmanita, Ani; Hurriyati, Ratih; Dirgantari, Puspo Dewi (Universitas Muhammadiyah Sorong, 2022)
The aims of this research is to measure the effect of gamification, variety of beverage products and prices onÂ buying interest of Fore Coffee consumers. The data collection technique was in the form of a questionnaire using a google form link that was distributed in several whatsapp groups. The results of the questionnaire were processed using the Structural Equation Modeling Analysis Technique with the SmartPLS application. The results show that the Gamifications contained in the application have an influence on consumer buying interest, seen from the results of testing the proposed model hypothesis. The T-value for the gamification variable is 2,934, which is greater than 1.96. The variety of beverage products found in the coffee application has an influence on consumer buying interest, seen from the results of hypothesis testing with a Tstatistic value of 3.646 which is greater than 1.96. Hypothesis testing shows that the price is not significant to the buying interest of front coffee consumers with a value of 1.94 which is smaller than 1.96. For further research, it can be developed with other gamification benefits embedded in online shopping applications, so that it can add to the repertoire of knowledge in the world of digital marketing.